Navigating Challenges and Transforming Radio Journalism in Indonesia: from New Order Control to Reform Opportunities - Yohanes Widodo; Ana Nadhya Abrar; Wisnu Martha Adiputra (Jurnal the Messenger, 2025)
Introduction: The evolution of radio journalism in Indonesia provides critical insights into its historical, technological, cultural, and political significance. As a medium, radio has been a cornerstone of public discourse and democratization, particularly during transformative periods such as the Reform Era. This study examines the evolution and contemporary challenges of radio journalism, with a specific focus on the operational realities of private radio stations in Indonesia.